Age differences in the takeover of vehicle control and engagement in non-driving-related activities in simulated driving with conditional automation. (September 2017) - Clark, Hallie; Feng, Jing
Highlights: We observed drivers' non-driving-related activities by allowing them to freely choose when, what task, and how to engage in these activities. Both younger (n = 17; age 18–35) and older (n = 18; age 62–81) drivers engaged in various activities during simulated automated driving. Younger and older drivers showed distinct preferences on the type of non-driving-related activities. Age and takeover notification interval, but not the level of activity-engagement, had significant impacts on driving performance. Older drivers responded to the takeover notifications as quickly as younger drivers. Abstract: High-level vehicle automation has been proposed as a valuable means to enhance the mobility of older drivers, as older drivers experience age-related declines in many cognitive functions that are vital for safe driving. Recent research attempted to examine age differences in how engagement in non-driving-related activities impact driving performance, by instructing drivers to engage in mandatory pre-designed activities. While the mandatory engagement method allows a precise control of the timing and mental workload of the non-driving-related activities, it is different from how a driver would naturally engage in these activities. This study allowed younger (age 18–35, mean age = 19.9 years) and older drivers (age 62–81, mean age = 70.4 years) to freely decide when and how to engage in voluntarily chosen non-driving-related activities during simulated driving with conditional automation. We coded video recordings of participants' engagement in non-driving-related activities. We examined the effect of age, level of activity-engagement and takeover notification interval on vehicle control performance during the takeover, by comparing between the high and low engagement groups in younger and older drivers, across two takeover notification interval conditions. We found that both younger and older drivers engaged in various non-driving-related activities during the automated driving portion, with distinct preferences on the type of activity for each age group (i.e., while younger drivers mostly used an electronic device, older drivers tended to converse). There were also significant differences between the two age groups and between the two notification intervals on various driving performance measures. Older drivers benefited more than younger drivers from the longer interval in terms of response time to notifications. Voluntary engagement in non-driving-related activities did not impair takeover performance in general, although there was a trend of older drivers who were more engaged in non-driving-related activities braking harder than those with low activity-engagement during the takeover.